(untitled) (ENTHYMEMA, 2012)
Narrative works show an innate awareness of the tension that comes from the necessity to give attention to different characters in different amount. The author proposes a theorethic model to face questions related to distributional choices in the 1800s novel. Categories such as space-character – the encounter/conflict between represented individual and narrative space – and system-characters – the disposition of multiple characters in a narrative structure – are introduced. These categories mean to overcome the scission that dominated the criticism on the character so far, divided into two antithetic positions: on one hand those who see the character as a mere formal device, on the other one those who emphasise its referential and human aspect. In proposing new categories we aim instead to re-establish the dialectics that bounds these two aspects of the fictional character, and, in particular, to shed a light on how the structural effects of the novel depend on the problem of representing minor characters, reduced to the two main paradigms of the eccentric and of the workers. The author interprets the novel’s devices and the structural disequilibria that come from the inclusion of the characters as the mirroring of the difficult relationship between inequality and democracy, which marked a whole century, the Nineteenth, where the bourgeoisie’s social mobility was the counterpart of the marginalisation of lower classes. The last part of this article is finally dedicated to the analysis of the character in works by Jane Austen, Dickens and Balzac.